2018
DOI: 10.1038/s41560-018-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and suppression of interfacial recombination for high-efficiency large-area pin perovskite solar cells

Abstract: The performance of perovskite solar cells (PSCs) is predominantly limited by non-radiative recombination, either through trap-assisted recombination in the absorber layer or via minority carrier recombination at the perovskite/transport layer interfaces. Here we use transient and absolute photoluminescence imaging to visualize all non-radiative recombination pathways in planar pin-type PSCs with undoped organic charge transporting layers. We find significant quasi-Fermi level splitting losses (135 meV) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
888
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 837 publications
(927 citation statements)
references
References 51 publications
37
888
1
1
Order By: Relevance
“…[33] Radiative recombination happens in a very short time, and normally appears as a power-law decay in the TRPL measurement, whereas the non-radiative recombination by monomolecular shows a monoexponential decay in the TRPL measurement. The second role played by ESM/HSM has been confirmed by Stolterfoht et al [34] who compared a range of ESMs and HSMs using the TRPL and absolute PL spectra measurement. [30] When the perovskite film is deposited adjacent to an ESM or HSM, the interpretation of TRPL data can be more complicated.…”
Section: Device Characterizationmentioning
confidence: 79%
See 1 more Smart Citation
“…[33] Radiative recombination happens in a very short time, and normally appears as a power-law decay in the TRPL measurement, whereas the non-radiative recombination by monomolecular shows a monoexponential decay in the TRPL measurement. The second role played by ESM/HSM has been confirmed by Stolterfoht et al [34] who compared a range of ESMs and HSMs using the TRPL and absolute PL spectra measurement. [30] When the perovskite film is deposited adjacent to an ESM or HSM, the interpretation of TRPL data can be more complicated.…”
Section: Device Characterizationmentioning
confidence: 79%
“…The more efficient in charge extraction, the more efficient in quenching of PL intensity. [34,35] The second role played by ESM/HSM has been confirmed by Stolterfoht et al [34] who compared a range of ESMs and HSMs using the TRPL and absolute PL spectra measurement.…”
Section: Device Characterizationmentioning
confidence: 86%
“…While the absolute locations of E F,e and E F,h are generally not accessible, the QFLS can be determined directly by means of absolute PL measurements . This methodology has been proven to be an efficient approach for quantifying recombination losses in the neat perovskite, multilayer assemblies or even complete perovskite solar cells …”
Section: Theorymentioning
confidence: 99%
“…During the past years, many studies have evaluated recombination in perovskites layers and suggested that defects at the perovskite surface or at grain boundaries as possible reasons for nonradiative recombination in neat perovskite layers . More recently, several studies have additionally highlighted the thorny problematic of the interfaces between the perovskite and charge transport layers in the actual device, due to the fast nonradiative recombination of carriers at or across these interfaces . Therefore, a detailed understanding of the losses and the underlying physical processes is essential in order to exploit the full potential of these materials in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in J sc can be attributed to the decrease in the series resistance as well as increase in the absorption at the active layer due to the near‐field enhancement and LSPR effect of the metal NPs . The recombination in the active layer and at the interface causes a loss in V oc . Moreover, reduced shunt resistance caused a decrease in the V oc .…”
Section: Resultsmentioning
confidence: 99%